To solve the equation 5/3 - 2x = 1/6, we can start by isolating the variable term, which is -2x.
First, we can subtract 5/3 from both sides of the equation:
(5/3 - 2x) - 5/3 = 1/6 - 5/3
Simplifying this equation gives:
-2x = 1/6 - 5/3
Next, we can find a common denominator for the two fractions on the right-hand side. The least common multiple of 6 and 3 is 6.
Multiplying the numerator and denominator of 1/6 by 2 and the numerator and denominator of 5/3 by 1, we have:
-2x = 2/12 - 10/12
Simplifying the equation further, we get:
-2x = -8/12
Now, we can simplify the fraction on the right-hand side to:
-2x = -2/3
To solve for x, we need to isolate the variable x.
Dividing both sides of the equation by -2 gives:
x = (-2/3) / -2
Simplifying this division gives:
x = 1/3
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 1/3.
What is the solution of the equation 5/3 -2x =1/6
1 answer